A Comparative Analysis between Food Affordability and Healthy Life Among The Rural and Urban People of Bangladesh - Prodipto Bishnu Angon; Md. Shafiul Islam (IPTEK The Journal for Technology and Science, 2022)
Good health depends on moderate and proper nutritional food. There is a noticeable difference in eating patterns between individuals living in rural and urban regions. The central aspect of this study is to make a comparative analysis of the health of rural and urban people with their eating habits. In February 2022, data were collected from 1,400 people in Bangladesh’s major cities through offline and online surveys and analyzed using IBM SPSS Statistics 25 and Microsoft Excel. Three types of correlation are brought out among the selected parameters, such as local people will be able to protect themselves from heart disease by consuming vegetables. The paper highlights the staple food of people of all ages in Bangladesh as well as their daily food intake time and quantity through a comprehensive survey. People will be able to adjust their health depending on the type and amount of food they consume, and they will also be able to know whether urban people are ahead of rural people and vice versa. This research can bring good health to the people by reviewing the food habits of the people of the village and the city.